2019
DOI: 10.3390/coatings9040263
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hydrolytic Degradation of the Sizing-Rich Composite Interphase

Abstract: Glass fiber-reinforced composites are exposed to hydrolytic degradation in subsea and offshore applications. Fiber-matrix interphase degradation was observed after the matrix was fully saturated with water and typical water absorption tests according to ASTM D5229 were stopped. Due to water-induced dissolution, fiber-matrix interphase flaws were formed, which then lead to increased water uptake. Cutting sample plates from a larger laminate, where the fibers were running parallel to the 1.5 mm long short edge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 58 publications
(129 reference statements)
1
33
0
Order By: Relevance
“…Because of this reduction of properties, especially locally high stresses around fibre breaks or fibre-matrix debondings of the transverse fibres are suggested to result in more severe defects locally. Furthermore, the presence of water inside the interphase is expected to destroy the strong covalent bonds between the silane coupling agents and the matrix, as well as reduce secondary molecular forces over time [50]. Additionally, as the interlaminar shear properties (strength and stiffness) of the composite also suffer noticeably (Table 3), the stress transferability between the fibres will decrease as well.…”
Section: Investigationmentioning
confidence: 99%
“…Because of this reduction of properties, especially locally high stresses around fibre breaks or fibre-matrix debondings of the transverse fibres are suggested to result in more severe defects locally. Furthermore, the presence of water inside the interphase is expected to destroy the strong covalent bonds between the silane coupling agents and the matrix, as well as reduce secondary molecular forces over time [50]. Additionally, as the interlaminar shear properties (strength and stiffness) of the composite also suffer noticeably (Table 3), the stress transferability between the fibres will decrease as well.…”
Section: Investigationmentioning
confidence: 99%
“…Although this work showed that applying TESPT using different methods enabling different types of fillers to be used as reinforcement fillers in rubber composites, its effect on long term durability has not been extensively studied. The durability of interfacial adhesion between filler and rubber matrix in service and under long‐term exposure to external environmental such as moisture, temperature and loading stress can degrade the interfacial adhesion as well as the properties of the constituent phases resulting in material failure 67,68 . Therefore, it is of great importance to understand the environmental aging of the filler‐rubber interphase in order to realize the full potential of TESPT treatment for fillers in natural rubber composites.…”
Section: Discussionmentioning
confidence: 99%
“…Images showing the opening space between adjacent fibers in the 90 -ply at 6.7% (d) and the appearance of intralaminar crack exactly in these regions (f). Volume dimensions: 2 × 2 × 4.5 mm 3 [Color figure can be viewed at wileyonlinelibrary.com] (0 -ply) also happen upon tensile loading, but as an isolated event without any correlation with the transverse cracks (Figure 4f). Further strain led to the appearance of crack bridging between the transverse matrix cracks, extending through the sample thickness under Mode I loading (Figures 3 and 4).…”
Section: Monitoring the Toughening Mechanisms In The Gfrp Compositesmentioning
confidence: 99%
“…[1] High level of favorable surface interactions between the components of polymer composites are crucial for an efficient load transfer from matrices to reinforcing agents, as well as a reduction of the damage effects caused by external agents, such as the accumulation of water in the interfacial region. [2,3] Several physicochemical treatments can tailor the interfacial strength and stability of polymer composites, including covalent grafting reaction, plasma discharge treatment, oxidation, and sylanization. [4][5][6][7][8][9][10][11] However, the construction of hybrid interfaces would not only affect adhesion, but also offer the possibility to impart new properties, such as enhanced conductivity, improved toughness, and stored active moieties as self-healing agents or bactericidal compounds.…”
Section: Introductionmentioning
confidence: 99%